2014
DOI: 10.1536/ihj.13-275
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Changes Following Experimentally-Induced Acute Myocardial Infarction in Rats

Abstract: SummaryRats with experimentally-induced acute myocardial infarction (AMI) have proven to be a clinically relevant model for visceral pain. As there are no behavioral data available on rats in the postinfarction period, we aimed to identify specifi c pain-related behavioral changes following AMI to increase the validity of the model. AMI was induced by left coronary artery ligation and pain-related behavior was analyzed using the open fi eld test (OFT) and elevated plus maze (EPM). Morphine was applied followin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 48 publications
1
2
0
Order By: Relevance
“…On a structural level, it was shown there is remodeling of neuronal networks in the medial PFC under the influence of stress [42]. Furthermore, according to findings of Banozic et al, anxiety like behavior can be demonstrated in a model of AMI [11]. In our current study the increase in beta band power was already significant during the first hour (H1) and remained increased during the whole four hours (D1) after isoprenaline administration.…”
Section: What Changes In Eeg Beta Band Power Could Tell Us?supporting
confidence: 75%
See 1 more Smart Citation
“…On a structural level, it was shown there is remodeling of neuronal networks in the medial PFC under the influence of stress [42]. Furthermore, according to findings of Banozic et al, anxiety like behavior can be demonstrated in a model of AMI [11]. In our current study the increase in beta band power was already significant during the first hour (H1) and remained increased during the whole four hours (D1) after isoprenaline administration.…”
Section: What Changes In Eeg Beta Band Power Could Tell Us?supporting
confidence: 75%
“…Namely, within 72 hours of AMI onset there is neuronal loss in the central nervous system (CNS), most importantly in the lymbic system, hypothalamus and brainstem [8,9]. Further, depression onset after AMI was corroborated by studies in rats looking at behavioral signs of anhedonia and despair 2 weeks post AMI that can be reversed by antidepressants [10][11][12]. Exploring sleep-related disturbances in rats two weeks post AMI revealed decreased slow wave sleep and decreased latency to rapid eye movement (REM) sleep onset previously recognized in patients with depression [12].…”
Section: Introductionmentioning
confidence: 99%
“…Inflammation and psychological stress modify behavior related to emotionality, pain (Cattaruzza et al, 2013 ; Banozic et al, 2014 ) and sickness (Zhang et al, 2014 ; Farzi et al, 2015 ). Increased activity in rats exposed to unpredictable chronic mild stress resembles the psychomotor agitation seen in patients with psychiatric disorders (Gronli et al, 2005 ).…”
Section: Discussionmentioning
confidence: 99%